Gut microbiota modulation and amino acid absorption by Lactiplantibacillus plantarum TWK10 in pea protein ingestion - Mon-Chien Lee; Chun-Hui Chiu; Yi-Chu Liao; Yi-Chen Cheng; Chia-Chia Lee; Chin-Shan Ho; Yi-Ju Hsu; Hsiao-Yun Chang; Jin-Seng Lin; Chi-Chang Huang (Current Research in Food Science)
For vegetarians or vegan athletes, improving the utilization of plant-based protein and the absorption of amino acids is crucial. This study explored the impact of combining pea protein with Lactiplantibacillus plantarum TWK10 and resistance training on amino acid absorption and exercise performance. Sixteen male and sixteen female participants were randomly assigned to either a control group (20 g of pea protein without TWK10) or a TWK10 group (20 g of pea protein combined with 1 × 1010 colony-forming units of TWK10). After 28 days of supplementation combined with resistance exercise training three times per week. All subjects underwent body composition and muscle strength performance, plasma and fecal samples were collected for microbiota analysis and blood amino acid concentrations. The TWK10 group showed a significant increase in muscle thickness and improvements were observed in 1 repetition maximum bench press, explosive, anaerobic power output compared to before the intervention, and were significantly higher than those in the control group (p < 0.05). TWK10 supplementation significantly increased the area under the curve and maximum concentration of branched-chain amino acids, essential amino acids, and total amino acids (p < 0.05). Furthermore, TWK10 supplementation effectively increased the richness of gut bacterial families. Our study demonstrated that the TWK10 significant increase in the abundance of specific bacterial families in the gut, resulting in increased pea protein amino acid absorption. Moreover, increasing muscle mass and significantly improving muscle thickness, muscle strength, power, and anaerobic capacity.